Zaranie, rozwój oraz perspektywy etyki środowiskowej – wybrane zagadnienia - Anna Marek-Bieniasz (Studia Ecologiae et Bioethicae)
The article is an attempt at presenting some aspects of the development of environmental ethics, i.e. the situation in which this discipline evolved, which is referred to as the ecological crisis. It presents the way in which this discipline was understood by its first representatives, their demands concerning both the ways in which it should be funded, and its further theoretical development. At the same time, the process of penetration of Albert Schweitzer's ethics of respect for life into the reflections of environmental ethicists is discussed. The author compares such ethics with the ethics of the most famous representative of this discipline in Poland, i.e. Henryk Skolimowski. The article also reveals some of the developmental trends of environmental ethics and lists its representatives. It also discusses the theses and assumptions of biocentric environmental ethics and draws attention to the prospects and the need for further development of this discipline.